2002
DOI: 10.1081/ss-120014433
|View full text |Cite
|
Sign up to set email alerts
|

Separation Performance of Supercritical Carbon Dioxide Extraction Column for the Citrus Oil Processing: Observation Using Simulator

Abstract: Phase behavior of limonene and linalyl acetate, which are principal constituents of terpenes and oxygenated compounds, respectively, in bergamot oil, with supercritical carbon dioxide (SC-CO 2 ) was observed by use of process simulator (SIMSCI PRO/II). Solubility of each pure component in SC-CO 2 was calculated by the Peng -Robinson equation of state. For a given calculating condition, the solubility of limonene was 2 -5 times higher than that of linalyl acetate. Process flow diagram for the citrus oil process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Researchers from this group observed that when performing continuous fractionation, the selectivity was not significantly influenced by the use of an external reflux (reflux mode). On the other hand, they found that the solvent-to-feed ratio, and feed-inlet position were important variables in the fractionation of citrus fruit essential oils [63][64][65]67,68,71,73]. In fact, better results were obtained operating the column in the stripping mode [66].…”
Section: Semi-batch Contacting Equipmentmentioning
confidence: 91%
“…Researchers from this group observed that when performing continuous fractionation, the selectivity was not significantly influenced by the use of an external reflux (reflux mode). On the other hand, they found that the solvent-to-feed ratio, and feed-inlet position were important variables in the fractionation of citrus fruit essential oils [63][64][65]67,68,71,73]. In fact, better results were obtained operating the column in the stripping mode [66].…”
Section: Semi-batch Contacting Equipmentmentioning
confidence: 91%
“…Multistage gas extraction in countercurrent columns has been considered as an alternative separation technique for the extraction and fractionation of liquid mixtures with potential applications in the food industry [60][61][62]. The applications include removal of terpenes from citrus oils [63][64][65][66][67][68][69][70][71][72], separation of fatty acids ethyl esters from butteroil, fish oil, and model mixtures [73][74][75], isolating of polycyclic aromatic hydrocarbon (PAH) oligomers [76], Isolation of antioxidant compounds from orange juice [77][78], deacidification of olive and rice bran oils [79][80][81][82], fractionation of fatty acids from palm fatty acid distillates [83][84], purification of fat-soluble substances (tocopherols, sterols, carotenes, and squalene) from palm oil, olive oil, soya deodorize distillates, olive oil deodorize distillates, and hexane extract of olive leaves [81,[85][86][87][88][89][90], fractionation of alcoholic beverages to obtain distillates with lower alcoholic content [91][92], separation of ethanol from aqueous solutions [93], separation of aroma constituents from aqueous solutions of apple, brandy, and wine-must aroma [94][95][96], fractionation of non-esterified alkoxyglycerols from shark liver oil…”
Section: Introductionmentioning
confidence: 99%